MULTIPOINT PROBLEM FOR PSEUDODIFFERENTIAL EQUATIONS - Klyus, Iryna; Vasylyshyn, Pavlo; Konovaliuk, Valentyna (Proceedings of National Aviation University (archive), 2015)
Correctness of the problem with multipoint conditions in time variable and frequency of the spatial coordinates for the partial differential, equations, not solved with respect to the highest derivative, with pseudodifferential operators is investigated. The conditions of existence and uniqueness of the problem solution, metric theorems on lower bounds of small denominators arising in the construction of the solution of the problem are proved.